'Happy' drug survival of adalimumab, etanercept and ustekinumab in psoriasis in daily practice care: results from the BioCAPTURE network. (1st November 2014) - van den Reek, J.M.P.A.; Zweegers, J.; Kievit, W.; Otero, M.E.; van Lümig, P.P.M.; Driessen, R.J.B.; Ossenkoppele, P.M.; Njoo, M.D.; Mommers, J.M.; Koetsier, M.I.A.; Arnold, W.P.; Sybrandy‐Fleuren, B.A.M.; et al.
Summary: Background: Drug survival is a marker for treatment success. To date, no analyses relating dermatological quality‐of‐life measures to drug survival have been published. Objectives: (i) To describe 1‐year drug survival for adalimumab, etanercept and ustekinumab in a daily practice psoriasis cohort, and (ii) to introduce the concept of 'happy' drug survival, defined as Dermatology Life Quality Index (DLQI) ≤ 5 combined with being 'on drug' at a specific time point. Methods: Data were extracted from a prospective registry. Drug survival was analysed using Kaplan–Meier estimates. 'Happy' drug survival was calculated, with data split into 'happy' (DLQI ≤ 5) vs. 'unhappy' (DLQI > 5) at baseline and months 3, 6, 9 and 12. Results: 249 treatment episodes were included (101 adalimumab, 82 etanercept, 66 ustekinumab). The 1‐year drug survival rates for ustekinumab, adalimumab and etanercept were 85%, 74% and 68%, respectively. Ustekinumab showed a better confounder‐corrected drug survival vs. etanercept [hazard ratio (HR) 3·8, P = 0·02] and a trend towards better survival vs. adalimumab (HR 2·3, P = 0·1). At baseline, the majority ( n = 115, 73%) was considered 'unhappy' and a minority 'happy' ( n = 42, 27%) (ratio 'happy':'unhappy' was 1 : 2.7). The percentage of treatment episodes with 'happy' on‐drug patients increased to 79% after 1 year. Conclusions: Ustekinumab showed a better overall drug survival than etanercept, and a trend towards a better overall drug survival than adalimumab. After 1 year, patients reported to be 'happy' in 79% of episodes and 'unhappy' in 21%. We introduced the new concept of 'happy' drug survival because the proportion of on‐drug patients with good quality of life is an important indicator for treatment success.